Quasi‐Static Compression Response and Energy Absorption of CNTF/EP Origami Thin‐Walled Tubes - Bowen Zhang; Chuanling Men; Ying Kong; Zhengqiang Lv; Changwei Li; Dongmei Hu (Advanced Materials Interfaces)
Abstract This study investigates the quasi‐static compression response and energy absorption characteristics of origami‐inspired thin‐walled tubes fabricated from carbon nanotube film/epoxy (CNTF/EP). The quasi‐static compression tests are performed on the origami tubes, square tubes, circular tubes, and thin‐walled tubes made from other common materials for comparison, and key mechanical performance indicators, including initial peak force (PF), energy absorption (EA), specific energy absorption (SEA), mean crushing force (MCF), and crushing load efficiency (CLE), are evaluated. The deformation modes of the tubes during compression are observed and analyzed, revealing four typical patterns. Among them, there are both good deformation modes and bad deformation modes, which significantly affect the compressive performance of the thin‐walled tube. Additionally, the effects of introducing creases at different positions on the quasi‐static compression behavior are explored. Tests are conducted to verify the reusability of the thin‐walled tubes. The origami tubes exhibited significant improvements in PF, SEA, and MCF after manual recovery and cyclic testing, indicating their potential for reusability. With excellent compressive energy absorption properties, foldability, and reusability, CNTF/EP origami thin‐walled tubes are suitable for various impact mitigation applications.